2019
DOI: 10.1038/s41598-018-38474-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear nanomedicine using Si nanoparticles as safe and effective carriers of 188Re radionuclide for cancer therapy

Abstract: Nuclear nanomedicine, with its targeting ability and heavily loading capacity, along with its enhanced retention to avoid rapid clearance as faced with molecular radiopharmaceuticals, provides unique opportunities to treat tumors and metastasis. Despite these promises, this field has seen limited activities, primarily because of a lack of suitable nanocarriers, which are safe, excretable and have favorable pharmacokinetics to efficiently deliver and retain radionuclides in a tumor. Here, we introduce biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…(i) In contrast to porous silicon nanostructures, laser-synthesized Si-NPs have ideal spherical shape and are low size-dispersed, which promises a much improved transport in biological systems in vivo [27]; (ii) Laser-synthesized Si-NPs can have a defect-rich polycrystalline structure, which conditions a much faster dissolution and excretion of these nanoparticles from the body in vivo (4-7 days [22,23] compared to more than 6 weeks in the case of porous silicon [35]); (iii) Laser-synthesized Si-NPs are produced in ultrapure deionized water, which excludes any contamination of nanoparticles by toxic by-products of synthesis, as it takes place in many alternative methods [11,12,16]; (iv) Laser-synthesized Si-NPs can offer a series of imaging [5,26] and therapy (Refs. [9,19,27]) modalities, which can be enabled in parallel with the considered photothermal modality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) In contrast to porous silicon nanostructures, laser-synthesized Si-NPs have ideal spherical shape and are low size-dispersed, which promises a much improved transport in biological systems in vivo [27]; (ii) Laser-synthesized Si-NPs can have a defect-rich polycrystalline structure, which conditions a much faster dissolution and excretion of these nanoparticles from the body in vivo (4-7 days [22,23] compared to more than 6 weeks in the case of porous silicon [35]); (iii) Laser-synthesized Si-NPs are produced in ultrapure deionized water, which excludes any contamination of nanoparticles by toxic by-products of synthesis, as it takes place in many alternative methods [11,12,16]; (iv) Laser-synthesized Si-NPs can offer a series of imaging [5,26] and therapy (Refs. [9,19,27]) modalities, which can be enabled in parallel with the considered photothermal modality.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, laser-synthesized Si NPs can be efficient sensitizers of therapeutic modalities such as PDT [7] and RF radiation-induced hyperthermia [9], as well as serve as carriers of therapeutic radionuclides [27]. Such a combination of different modalities in one Si-based nanoformulation looks as an effective strategy to develop novel theranostic (therapy + diagnostics) agents for biomedical applications.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…For the synthesis of PdAu NPs we adapted methods of ultrashort laser ablation and fragmentation in liquid ambience, which were earlier used for the preparation of bare Au [16][17][18][19] and Si 32,33 NPs. Our approach for nanoalloy synthesis was based on the co-fragmentation of the mixture of two types of metallic nanoparticles.…”
Section: Synthesis and Characterization Of Bare Pdau Nanoparticlesmentioning
confidence: 99%
“…Making possible fast production of bare (uncovered) NPs in colloidal state with almost any composition, pulsed laser ablation in liquids [12][13][14][15][16][17] (PLAL) provides one of best alternatives to satisfy the above-stated demands. As an example, we recently showed that the technique of femtosecond laser ablation in liquids can be used for the fabrication of a variety of ultrapure, biologically-friendly nanomaterials, including gold NPs [16,[18][19][20][21][22], titanium nitride (TiN) NPs [23], silicon NPs [24][25][26][27] and organic polymer NPs [28]. In many cases, such nanoparticles can provide superior properties for catalytic [20], energy and biomedical [29,30] applications, compared to nanomaterials synthesized by conventional chemical methods, and other methods.…”
Section: Sm Oxide Powder and Preparation Of Target For Ablationmentioning
confidence: 99%